2006
DOI: 10.1038/sj.ejhg.5201618
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism for mitochondrial DNA polymorphic variants in placenta has implications for the feasibility of prenatal diagnosis in mtDNA diseases

Abstract: Women who have had a child with mitochondrial DNA (mtDNA) disease need to know the risk of recurrence, but this risk is difficult to estimate because mutant and wild-type (normal) mtDNA coexist in the same person (heteroplasmy). The possibility that a single sample may not reflect the whole organism both impedes prenatal diagnosis of most mtDNA diseases, and suggests radical alternative strategies such as nuclear transfer. We used naturally occurring mtDNA variants to investigate mtDNA segregation in placenta.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…In addition, mtDNA copy number varied approximately fivefold (see online figure 3). Similarly, we saw a statistically significant variation of similar magnitude in the distribution of one of two polymorphic variants, consistent with previous data 37. We previously demonstrated that the average level of polymorphic heteroplasmic mtDNA variants is very similar in mother, cord blood and placenta.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, mtDNA copy number varied approximately fivefold (see online figure 3). Similarly, we saw a statistically significant variation of similar magnitude in the distribution of one of two polymorphic variants, consistent with previous data 37. We previously demonstrated that the average level of polymorphic heteroplasmic mtDNA variants is very similar in mother, cord blood and placenta.…”
Section: Discussionsupporting
confidence: 92%
“…In preliminary data from human blastomeres41 42 (supplementary information 2), we provide some support for earlier findings from mouse43 and human44 that heteroplasmy in blastomeres varies more between embryos than within embryos. Nevertheless, in the absence of extensive data, it may be necessary to take two samples at CVS37 because of the considerable variation in the level of mtDNA mutant that we documented in placental patches. This also argues for repeated sampling at PGD, say two separate blastomeres.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HV1 length heteroplasmy, all of these samples contained a T-to-C transition at position 16189, which resulted in an unbroken series of 10Cs. This long C-stretch was considered to lead to poor replication fidelity and consequently length heteroplasmy [21,22]. According to a previous report [23], length heteroplasmy in the HV1 region can be easily identified by the dramatic decrease in sequencing quality that occurs beyond the heteroplasmic region.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, length heteroplasmies in the HV2 region do not contain a T-to-C transition and do not show significant interference of sequencing analysis in the C-stretch region. In sequencing electropherograms, the heteroplasmic ratios in HV2 vary greatly from sample to sample (ranging from no detectable heteroplasmy, through barely discernible, to pronounced heteroplasmy) [22]. Therefore, length heteroplasmies in the HV2 region cannot be identified only from sequencing electropherograms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation